2015
DOI: 10.7603/s40730-015-0029-6
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Bone Marrow Stem Cells combined with Allograft Cancellous Bone in Treatment of Nonunion

Abstract: Abstract-Autologous cancellous bone graft is currently used as a gold standard method for treatment of bone nonunion. However, there is a limit to the amount of autologous cancellous bone that can be harvested and the donor site morbidity presents a major disadvantage to autologous bone grafting. Embedding viable cells within biological scaffolds appears to be extremely promising. The purpose of this study was to assess the outcome of autologous bone marrow stem cells combined with a cancellous bone allograft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…Nine studies evaluated the use of cBMA in bone healing summarized in Table 4 [ 25 - 33 ]. Eight of nine studies reported on the use of cBMA in either non-union or delayed union.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nine studies evaluated the use of cBMA in bone healing summarized in Table 4 [ 25 - 33 ]. Eight of nine studies reported on the use of cBMA in either non-union or delayed union.…”
Section: Resultsmentioning
confidence: 99%
“…All studies reported either lower or similar complication rates post-operatively in groups that received cBMA compared to groups receiving no additional treatment. Bone consolidation and time to bone union was improved in patients receiving cBMA, with faster healing rates when compared to patients in the autograft group[ 33 ]. One study found a significantly lower number of progenitor cells in patients who did not achieve union as well as a negative correlation between the time needed to obtain union and the concentration of colony forming units in the graft[ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since this time, orthopedic applications of stem cells have expanded significantly; yet, almost all clinical applications make use of autologous bone marrow including treatments for femoral head necrosis (Mai Dac Viet, 2010;Nguyen Thi-Thu Ha, 2013), bone defect and short limb (Nguyen Van Luong, 2010), tibia non-unions (Nguyen Manh Khanh, 2010), long bone non-union (Le Van Doan, 2011;Nguyen Thi-Thu Ha, 2013;Thua et al, 2015a), long bone diaphyseal non-unions (Ngo Ba Toan, 2012, 2014, joint diseases (Duong Dinh Toan, 2013a;Ly Tuan Khai, 2013;Nguyen Thanh Binh, 2012), limb lengthening (Nguyen Thi-Thu Ha, 2013), knee osteoarthritis (Duong Dinh Toan, 2013b;Duong Dinh Toan, 2014) and delayed or non-union bone (Thua et al, 2015b). The common property of these studies is use of non-expanded autologous stem cells; each used concentrated autologous bone marrow generated using a centrifuge-based method.…”
Section: Orthopedic Disordersmentioning
confidence: 99%